Heterotrophic nitrification-aerobic denitrification performance in a granular sequencing batch reactor supported by next generation sequencing - Bucci, Paula Lorena (2021)
Several nitrogen transformation processes occur in wastewater treatment; among them, heterotrophic nitrification-aerobic denitrification (HNAD) has not been adequately quantified. In the present study, a comprehensive analysis of the simultaneous ammonia and organic carbon removal was carried out in an aerobic granular sequencing batch reactor (SBR) operated under feast/famine regime. For this, biological processes, microbial community composition and metabolic pathways were evaluated. Mass balances allowed estimating the ammonia assimilation and simultaneous nitrification and denitrification (SND). Better SND process (55%) was achieved in starvation period involving that denitrification driven by intracellular carbon reserves is more efficiently coupled to the ammonia oxidation with regard to external carbon-driven denitrification. Proton balances and titration monitored the organic carbon and nitrogen removal. High abundance of HNAD bacteria, Diaphorobacter sp. and Flavobacterium sp., and Zoogloea sp. aerobic denitrifier was detected by next generation sequencing (NGS) technology. Bioinformatics analysis predicted enzymes involved in nitrogen transformation pathways present in Phylogenetic investigation PYCRUSt database. Heterotrophic nitrification took place involving detoxification against ammonia. Non-limiting nitrate and high oxygen concentrations were favorable for aerobic denitrifiers. HNAD was the main process responsible for the biological nitrogen removal according to NGS and operational conditions given by high dissolved oxygen and low COD:NO3−-N ratio.